2013
DOI: 10.2217/nnm.12.204
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ε-Caprolactone)–Carbon Nanotube Composite Scaffolds for Enhanced Cardiac Differentiation of Human Mesenchymal Stem Cells

Abstract: Aim To evaluate the efficacy of electrically conductive, biocompatible composite scaffolds in modulating the cardiomyogenic differentiation of human mesenchymal stem cells (hMSCs). Materials & methods Electrospun scaffolds of poly(ε-caprolactone) with or without carbon nanotubes were developed to promote the in vitro cardiac differentiation of hMSCs. Results Results indicate that hMSC differentiation can be enhanced by either culturing in electrically conductive, carbon nanotube-containing composite scaffo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(50 citation statements)
references
References 35 publications
1
49
0
Order By: Relevance
“…Based on these studies Crowder et al proposed the addition of multiwall carbon nanotubes (MWCNTs) in PCL [134]. This way the conductivity was up to 35 mS/cm, depending on the composition.…”
Section: Co-electrospinning With Conductive Materialsmentioning
confidence: 99%
“…Based on these studies Crowder et al proposed the addition of multiwall carbon nanotubes (MWCNTs) in PCL [134]. This way the conductivity was up to 35 mS/cm, depending on the composition.…”
Section: Co-electrospinning With Conductive Materialsmentioning
confidence: 99%
“…Membranes only and membranes coated with purified type I collagen were secured into snapwell inserts. 10 5 TIME cells were seeded onto each membrane and grown for 6 days. TEER was measured every 2 days after 48 hours from seeding.…”
Section: Transendothelial Electrical Resistance (Teer)mentioning
confidence: 99%
“…PEG is a biocompatible, hydrophilic polymer that can repel protein and cells [9]. In our previous studies we showed that physicochemical, mechanical, and bioactive properties of electrospun fiber scaffolds can be tuned to promote cell growth and differentiation by combining these two components with different mole percentages [10,11].…”
mentioning
confidence: 99%
“…18 In brief, the total protein of the cell-scaffold constructs was prepared using lysis buffer (Tiandz, Beijing, People's Republic of China). For determination of Western blotting by SDS-PAGE, 100 µg total protein was separated by SDS-PAGE electrophoresis, and anti-α-SA (Abcam), anti-β1-integrin (Abcam), anti-phospho-Smad 2 (Cell Signaling Technology, Beverly, MA, USA), and anti-Smad 2 antibodies (Cell Signaling Technology) were used to incubate the polyvinylidene difluoride membrane with total protein.…”
Section: Protein Isolation and Western Blot Analysismentioning
confidence: 99%
“…Poly(ε-caprolactone)-CNT composite scaffolds have been confirmed to enhance the adhesion and cardiac differentiation of human mesenchymal stem cells. 18 Numerous reports have shown that CNTs exert beneficial impacts on lineage specification of stem cells; nevertheless, the definite role of CNTs in regulation of cardiac differentiation of BASCs, and especially the underlying molecular mechanism, has not yet been revealed. Unveiling these events is a key step necessary for the application of CNTs in clinical scenarios for cardiac regeneration.…”
Section: Introductionmentioning
confidence: 99%